2022
DOI: 10.3389/fvets.2022.1067880
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic factors affecting the meat quality and flavor of Inner Mongolian lambs: A review

Abstract: The Inner Mongolia Autonomous Region ranks first among the five major pastoral areas in terms of lamb breeding of China. The Inner Mongolia Autonomous Region has a vast territory, with many famous grasslands and thousands of forage plants and multiple local high-quality lamb breeds. After hundreds of years of artificial breeding and improvement, Mongolian sheep have developed many varieties. Different diets, feeding and treatment methods have effects on the production performance, lipid deposition and flavor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 125 publications
1
4
1
Order By: Relevance
“…The results in this study disagreed with Gashu et al (2017) and Claffey et al (2018) who reported that intact lambs indicate significantly better feed conversion ratio than castrated lambs that caused by sex hormone which lead to increase the efficiency of dietary nutrient utilization, through enhancing feed efficiency (Ismail 2006). Liu et al (2022) showed that the FCR of rams was 12-15% higher than that of castrates, which tends to be similar to our results which showed an improvement of the FCR by 8%.…”
Section: Effects Of Feeding Systems and … Abdulkarim Amad Et Alcontrasting
confidence: 94%
See 2 more Smart Citations
“…The results in this study disagreed with Gashu et al (2017) and Claffey et al (2018) who reported that intact lambs indicate significantly better feed conversion ratio than castrated lambs that caused by sex hormone which lead to increase the efficiency of dietary nutrient utilization, through enhancing feed efficiency (Ismail 2006). Liu et al (2022) showed that the FCR of rams was 12-15% higher than that of castrates, which tends to be similar to our results which showed an improvement of the FCR by 8%.…”
Section: Effects Of Feeding Systems and … Abdulkarim Amad Et Alcontrasting
confidence: 94%
“…On the other hand, the disappearance of the significant differences between intact and castrated lambs regarding the total and daily weight gain in this study it might be due to that the castrated lambs in the last stages of the experiment grew rapidly, but they could not reach the same growth rate of intact lambs which in accordance with the findings of Melches et al, (2006) who mentioned that lambs are also able to compensate for weight loss post-castration. These results are in consistence with earlier studies who confirmed that intact lambs were significantly superior in average total and daily weight gain comparing to castrated ones, the predominance of intact lambs is caused by the stimulation of sex hormones testosterone (Seideman et al 1982;Hanrahan 1999;Liu et al 2022). Moreover, Kiyma et al, 2000 reported that an improved growth rate in intact lambs could be associated ISSN: 2537-0804 eISSN: 2537-0855…”
Section: Castration and Lamb's Performancesupporting
confidence: 88%
See 1 more Smart Citation
“…For a long time, the development of animal husbandry in grassland areas has been heavily dependent on natural grassland, which has led to long-term overgrazing, grassland degradation and desertification, resulting in an imbalance in grassland ecological and productive functions ( Bardgett et al, 2021 ). However, in most agricultural areas, the total house-feeding system has been widely adopted, which has resulted in lower livestock activity, reduced mutton quality and more severe disease ( Liu et al, 2022 ). Modern grassland and animal husbandry are new industrial patterns, a remarkable feature of which is the combination of planting and animal husbandry ( Hou & Zhang, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Goat meat quality is influenced by various factors, which can be divided into nongenetic and genetic factors. Non-genetic factors, such as the external environment, feeding management and slaughtering methods, vary considerably across the industry [2]. Conversely, genetic factors, including the breed, individual characteristics and tissue parts, exhibit less variability [3,4].…”
Section: Introductionmentioning
confidence: 99%